Assessment of Five Heavy Metals in Water, Sediment and Catfish-Clarias gariepinus from River Benue at Ibi, Taraba State, Nigeria - Johnson, Gani; Atoshi, Ago Mikyitsabu; Yakubu, Joshua; Audu, Stephen I. (African Multidisciplinary Journal of Sciences and Artificial Intelligence, 2024)
Water is also a vital resource for agriculture, manufacturing and other human activities. In urban areas, the careless disposal of industrial effluents and other wastes into rivers may contribute greatly to the poor quality of river water. This research is to assess the level of heavy metals (Cd, Cu, Mn, Ni, Pb and Zn) in Catfish-Clarias gariepinus and the sediment from River Benue at Ibi, Taraba state, Nigeria. The level of heavy metals in water, sediment and catfish from the study area were assess and the estimate contamination factor and pollution load index in the sediment of the study area was also access and compared with the WHO results and other relevant standards. The results shows that the concentration of heavy metal in fish was within the WHO permissible limits. Also the concentration of Pb, Zn and Ni in catfish were significantly (P≤0.05) higher compared to the metals but they were within the WHO permissible limits except for Cd. Heavy metal concentrations in sediment were within the acceptable WHO and USEPA limits, except for Cd, and Mn. PLI values for sediment from all the sites were less than one, implying that the sediment was unpolluted. The persistence of heavy metals in water, fish and sediment samples from the studied areas over time might lead to potential health risk on both humans and aquatic lives via food ingestion. Changes in water and sediment chemistry might be responsible for the variations in the chemical properties of sediment, water and fish.